Evaluation of the functional properties of promising Dioscorea trifida L. waxy starches for food innovation - Pérez, E.; Rolland Sabaté, Agnès; Gilbert, O.; Segovia, X; Sánchez, T.; Reynes, M; Dufour, D.L. (Hindawi Limited, 2011)
Few natural waxy starches are offered to the industry demand. Therefore, the morphological, physical, and chemical characteristics of “Mapuey” waxy starch were assessed. Amylose contents of starches isolated from Dioscorea trifida L. (“Mapuey”) landraces cultivated in the Amazons of Venezuela were lower (<8.1%) than commercial Mapuey starch (>8.7%). DSC onset gelatinization temperatures varied from 71.1 to 73.2°C. All starches exhibited B-type patterns, with degrees of crystallinity varying from 28% to 33%. The highest crystallinity was found for the starches exhibiting the highest amylose content. At 90°C, solubility and swelling power varied from 2.3 to 4.3% and 20.9 to 32.8%, respectively. Gel clarity was variable from 20.8 to 62.1%. A 5% starch suspension induced a high RVA peak viscosity between 1667 and 2037?cP. This natural waxy yam resource is a promising ingredient for food industry.